Aphrodisiac activity of ethanolic root extracts of Acacia pycnantha (Golden Wattle) in healthy male Wistar rats - Enyohwo Dennis Kpomah; Owo Gogo James; Bridget Kpomah (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: This study examines the aphrodisiac potentials of Acacia pycnantha in male Wistar rats, aiming at its effects on sexual behaviour, serum free testosterone and serum calcium concentrations. Materials & Methods: A. pycnantha roots were extracted using ethanol. Twenty male rats, averagely weighing 250.44 ± 8.72 g, were divided into four groups of five rats per group. Group 1, which is the control received normal saline (vehicle), group 2, the positive control, received 5 mg/kg of Yohimbine; and groups 3 and 4 received 50 mg/kg and 100 mg/kg of A. pycnantha, respectively. All test drugs were orally administered using an intragastric tube, and the treatment protocol lasted for 14 days. Sexual behaviour was assessed by measuring mounting frequency, intromission frequency, erection duration, and latency period. Serum-free testosterone and calcium concentrations were also measured. Data were analyzed using one-way ANOVA with Tukey’s post-hoc test to compare means and Pearson’s correlation to determine relationships between hormone concentrations and sexual behaviour indices. Results: Both low and high doses of A. pycnantha significantly amplified mounting frequency, intromission frequency, and erection duration while decreasing the latency period compared to the control group, with the high-dose group showing the most prominent effects. Serum-free testosterone concentrations were significantly elevated (p < 0.05) in both treated groups, with the high-dose group exhibiting the greatest increase. Additionally, serum calcium concentrations were significantly higher (p < 0.05) in the treated groups, with the high-dose group showing the most substantial increase. Pearson’s correlation analysis revealed strong positive correlations between testosterone concentrations and sexual behaviour parameters, and moderate to strong positive correlations between calcium concentrations and sexual behaviour parameters. Conclusion: A. pycnantha demonstrated significant aphrodisiac activity by enhancing sexual behaviour, elevating serum-free testosterone concentrations, and increasing serum calcium concentrations in male Wistar rats.